2000
DOI: 10.1143/jjap.39.6478
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Copper Oxide and β-Diketone for In situ Cleaning of Metal Copper in a Copper Chemical Vapor Deposition Reactor

Abstract: A detection of the stacked integrated Sachs-Wolfe (ISW) signal in the CMB of rare superstructures identified in the SDSS Luminous Red Galaxy catalogue has been reported at very high statistical significance. The magnitude of the observed signal has previously been argued to be more than 3σ larger than the theoretical ΛCDM expectation. However, this calculation was made in the linear approximation, and relied on assumptions that may potentially have caused the ΛCDM expectation to be underestimated. Here we upda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…One study suggests that the gas-phase reaction of hfacH with porous CuO wires between 170 and 240 °C occurs in a multistep process beginning with coordination of hfacH to Cu, forming an intermediate adsorbed Cu-hfac species (E A ) 44 kJ/mol). 31 Two neighboring Cu-hfac species react disproportionately to generate volatile Cu(hfac) 2 (E A ) 81 kJ/mol). A similar mechanism has been reported in the high-temperature (∼300 °C) gas-phase reaction of Pd(hfac) 2 with Cu metal to form Pd metal and Cu(hfac) 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study suggests that the gas-phase reaction of hfacH with porous CuO wires between 170 and 240 °C occurs in a multistep process beginning with coordination of hfacH to Cu, forming an intermediate adsorbed Cu-hfac species (E A ) 44 kJ/mol). 31 Two neighboring Cu-hfac species react disproportionately to generate volatile Cu(hfac) 2 (E A ) 81 kJ/mol). A similar mechanism has been reported in the high-temperature (∼300 °C) gas-phase reaction of Pd(hfac) 2 with Cu metal to form Pd metal and Cu(hfac) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This is lower than the 81 kJ/mol activation energy reported for the proposed disproportionation reaction of two Cu-hfac moieties in gas-phase CuO etching between 170 and 240 °C. 31 with hfacH in the gas phase and in scCO 2 are likely similar, but favorable solvent interactions enable analogous reactions to proceed at lower temperatures in scCO 2 . These solvation forces could act to stabilize intermediate species, thus reducing the activation barrier and facilitating low-temperature etching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p K a of the β-diketone and the coordinating ability of the conjugate ion will dictate the thermodynamic driving force for the removal of the surface bound species. While we have not experimentally observed surface bound M(hfac) intermediates, on the basis of gas-phase studies, , it is reasonable to propose that eq 8 proceeds via exchange of the surface-bound M(OAc) and M(O- t- Bu) species to produce surface-bound M(hfac). To ultimately extract a M(II) ion from the surface, it is necessary for two hfac - ligands to coordinate to a single M(II) ion and for the M(hfac) 2 complex, produced at the metal surface, to dissolve into solution.…”
Section: Resultsmentioning
confidence: 76%
“…Recently, we reported that copper metal can be oxidized and chelated in CO 2 media using ethyl peroxydicarbonate (EPDC) as an oxidant with a β-diketone chelating agent (eq 1) . This observation, which builds upon extensive studies of vapor phase etching of copper metal and oxidized copper species with β-diketone chelating agents, has opened the possibility of a CO 2 -based CMP technology for copper. The CO 2 solution reaction medium and the soluble oxidant allow these etching reactions to be conducted at low temperatures relative to the vapor phase reactions…”
Section: Introductionmentioning
confidence: 99%